Carcinogenic, ethanol, acetaldehyde and noncarcinogenic higher alcohols, esters, and methanol compounds found in traditional alcoholic beverages. A risk assessment approach. (2020) - Kokkinakis, Manolis; Tsakiris, Ioannis; Tzatzarakis, Manolis; Vakonaki, Elena; Alegakis, Athanasios; Papachristou, Stella; Karzi, Vasiliki; Kokkinaki, Aikaterini; Goumenou, Marina; Kallionakis, Manolis; Kalogeraki, Alexandra
Graphical abstract: Highlights: Alcoholic beverages (both bottled and bulk) may introduce risk to human health, for carcinogenic compounds (MOET). Bottled alcoholic beverages are safer than those produced in buck quantities, for noncarcinogenic compounds (HRI). Commercial fermentation and distillation processes provide a controlled environment compared to home made distillates. Abstract: Greek fermentation and distillation industries produce traditional spirit beverages, such as tsipouro and tsikoudia, consumed both in bottles and bulk quantities by the general population or tourists. The same spirits are also produced by individuals at home since previous centuries, as a part of the local culture but mainly due to the Greek agricultural sector unique characteristics (small cultivation areas with great number of farmers). In this study, the concentrations of carcinogenic compounds: ethanol and acetaldehyde; and noncarcinogenic: higher alcohols (1-propanol, isobutanol, and isoamyl alcohol), esters (ethyl acetate), and methanol were measured to estimate the potential cancer risk and daily intake of these compounds. The margin of exposure (MOE) of carcinogenic compounds was found to be less than 500 (mean value), well below the toxic threshold of 10, 000, above which there is not public concern, as suggested by the European Food Safety Authority. Additionally, through risk assessment of noncarcinogenic compounds, we identified two specific compounds in-bulk spirits (produced by individuals), namely ethyl acetate and isobutanol, with health risk index (HRI) greater than 1 (indicating a possibility to induce side effects by consumption of high amounts). Our results indicate that bottled spirits, which are produced in a controlled environment (alcohol industries), showed higher human safety level in terms of both carcinogenic and noncarcinogenic risk assessment studies, comparing to bulk beverages produced by individuals (with out strict regulations).